Implementation Of Evidence-Based Practice-Based Nursing Care - Robiul Fitri Masithoh; Noyumala Noyumala; Yona Sahalessy; Susi Susanti; Masrikat Maya Diana Claartje (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Evidence-Based Evidence-Based Practice (EBP) is an approach to nursing practice that integrates the best scientific evidence, nurses' clinical expertise, and patient values and preferences. The implementation of EBP-based nursing care is expected to improve the quality of care and patient safety. However, in practice, the implementation of EBP by nurses still faces various challenges. This study aims to determine the implementation of Evidence-Based Nursing Care. Practice in nursing services. This study uses a quantitative method with a descriptive analytical design and a cross-sectional approach. Sectional. The research sample was nurses in health care facility X. Data were collected using questionnaires and analyzed univariately and bivariately. The results showed that most nurses had implemented EBP-based nursing care in a good category, but there were still nurses who had not optimally utilized scientific evidence. The conclusion of this study is that the application of EBP in nursing care needs to be continuously improved through education and organizational support.